Students' unions, consumerism and the neo-liberal university. Issue 8 (16th November 2016) - Brooks, Rachel; Byford, Kate; Sela, Katherine
Abstract : This article explores the economic relationships between individual students' unions and their wider institutions, and the ways in which they articulate with a pervasive consumerist agenda across the higher education sector. We draw on data from a UK-wide study to argue that students' unions have an ambivalent relationship with consumerist discourses: on the one hand, they often reject the premise that the higher education student is best conceptualised as a consumer; yet, on the other, they frequently accept aspects of consumerism as a means of, for example, trying to protect their independence and autonomy. We explore whether this particular form of positioning with respect to consumerism is best conceptualised as a form of resistance, or whether it has become extremely difficult for students' unions to take up any other position in a system that is driven by market logic.